Enhancing Auditor Reputation Through CSR Activities and Their Impact on Audit Firms Client Base Growth - Zhoulie, Lin; Williams, Quent (Inovasi Analisis Data, 2025)
Purpose: This study aims to investigate the relationship between audit firms’ corporate social responsibility (CSR) activities and their reputations, as well as the impact of this on the audit firms’ abilities to gain and keep clients. The article examines the need for corporates to engage in corporate social responsibility (CSR) in order to enhance their reputations, potentially extending the same rationale to audit firms, as CSR engagement for corporates and audit firms are likely to have different implications on their client base.Method: Using a quantitative approach, a sample of audit firms was analyzed for a three years’ period. Using regression analysis, the study examined whether CSR involvement and intensity influence client acquisition and whether firm size and profitability moderate this relationship.Findings: Audit firms with higher CSR engagement are shown to have a significant increase in their client base. CSR activities build firm reputation, wherein the stakeholders are able to trust the company and also manage to stand out in the competitive market. Furthermore, this relationship is positively moderated by both firm size and profitability.Novelty: CSR impacts on marketing have been studied for other industries, but its importance within the audit industry is unique.Implications: The results indicate that audit firms may strategically allocate their resources towards CSR activities to align themselves with the competitive advantage and gain client advantage in the market. In addition, it underlines the need for alignment between CSR strategies and firm resources for the long-term growth and sustainability of the competitive advantage